The Stiffness‐Sensitive Transcriptome of Human Tendon Stromal Cells (Adv. Healthcare Mater. 7/2023). Issue 7 (13th March 2023) - Hussien, Amro A.; Niederoest, Barbara; Bollhalder, Maja; Goedecke, Nils; Snedeker, Jess G.
Abstract : Matrix Stiffness Extracellular matrix stiffness‐sensing studies are typically carried out using cells that have acquired "mechanical memory" through progressive passaging in rigid mechanical environments, e.g., tissue culture plastic (TCP). This confounds the mechanistic experiments that investigate matrix stiffness‐driven mechanosensing programs. In article 2101216, Jess G. Snedeker and co‐workers report the formulation of a mechano‐variant silicone‐based platform with tunable elasticity and tendon‐like elastic moduli, and with optimized chemistry to make it amenable to large‐scale cell expansion practices.